Proteasome inhibitors in AL amyloidosis: focus on mechanism of action and clinical activity - Jelinek, T; Kryukova, E; Kufova, Z; Kryukov, F; Hajek, R (Hematological oncology, 2017)
Proteasome inhibitors are the backbone in the treatment of multiple myeloma with 3 of its representatives (bortezomib, carfilzomib, and ixazomib) having already been approved. There is a different situation altogether in the treatment of amyloid light chain (AL) amyloidosis where owing to the rarity of this entity neither of these drugs has currently gained approval. Amyloid light chain plasma cells are possibly more vulnerable to bortezomib than myeloma plasmocytes because of a slightly distinct mechanism of action, which is described in depth in this manuscript. Bortezomib is highly active and rapidly effective as a single agent and even more potent in combination with dexamethasone and alkylators. Bortezomib-based regimens have become a standard part of the initial treatment of AL amyloidosis in the majority of centers. We have reviewed all available data on bortezomib in various combinations and settings. Carfilzomib seems to be effective but also toxic in these fragile patients with a high rate of cardiac events. Oral ixazomib has shown a surprisingly high efficacy with manageable toxicity and has received the Food and Drug Administration Breakthrough Therapy designation in 2014 for relapsed AL amyloidosis patients. In this review we have comprehensively described the current available knowledge of these 3 proteasome inhibitors and their use in AL amyloidosis.
Keywords: Immunoglobulin Light-chain Amyloidosis; Proteasome Inhibitors; mnohočetný myelom; ixazomib; multiple myeloma; carfilzomib; bortezomib; Humans; inhibitory proteasomu; Multiple Myeloma; Amyloidosis; primární amyloidóza; lidé; NEOD001